2022
DOI: 10.1002/art.41949
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Rheumatic Immune‐Related Adverse Events and De Novo Inflammatory Arthritis After Immune Checkpoint Inhibitor Treatment for Cancer

Abstract: Objective. To identify predictors of rheumatic immune-related adverse events (irAEs) following immune checkpoint inhibitor (ICI) treatment for cancer.Methods. We performed a case-control study to predict the occurrence of rheumatic irAEs in cancer patients who initiated ICI treatment at Mass General Brigham and the Dana-Farber Cancer Institute between 2011 and 2020. We screened for the presence of rheumatic irAEs by reviewing the medical records of patients evaluated by rheumatologists or those prescribed nong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 44 publications
0
13
1
Order By: Relevance
“…61.5% of patients with inflammatory arthritis induced by ICI had at least one SE allele vs. 41.2% of controls ( 16 ). A very recent study ( 21 ) reported that those patients with melanoma, genitourinary cancer, with pre-existing non-rheumatic autoimmune diseases and who received combination therapy were predictors for the development of rheumatic irAE.…”
Section: Discussionmentioning
confidence: 99%
“…61.5% of patients with inflammatory arthritis induced by ICI had at least one SE allele vs. 41.2% of controls ( 16 ). A very recent study ( 21 ) reported that those patients with melanoma, genitourinary cancer, with pre-existing non-rheumatic autoimmune diseases and who received combination therapy were predictors for the development of rheumatic irAE.…”
Section: Discussionmentioning
confidence: 99%
“…In one retrospective study, ICI-arthritis was found to be more common in patients with melanoma and genitourinary cancers than in patients with lung cancer, more common with combination ICI than with anti-PD1 monotherapy, and more common in patients with a history of a non-rheumatic autoimmune condition. 17 Patients with ICI-arthritis are more likely than the general population to carry at least one RA-associated HLA allele (referred to as the “shared epitope”) though they are less likely to be homozygous for the allele than RA patients. 18 …”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
“…We reviewed the literature through March 2022 to identify published approaches to ICI-arthritis management (See Supplement for search strategy and Supplemental Tables 1 and 2 ). We identified 15 case series (“case series”) with >3 patients that included patient level data 20 , 29 , 30 , 37–48 and 11 observational cohort studies (“cohort studies”) without individual patient level data 12 , 13 , 17 , 21 , 49–55 encompassing 595 ICI-arthritis and 95 ICI-PMR patients. Only 3 of the cohort studies were prospective, 12 , 13 , 52 and there were no randomized controlled trials, emphasizing the low quality of the evidence.…”
Section: Ici-arthritis Managementmentioning
confidence: 99%
“…A large study showed that melanoma, genitourinary cancer, preexisting non-rheumatic autoimmune diseases and receiving combination therapy at baseline were considered to be potential predictors of the development of inflammatory arthritis. 43 The results of this study have also been validated in non-U.S. populations. 44 , 45 Cappelli et al 32 evaluated the related HLA type I and type II genes in patients with inflammatory arthritis irAEs, including A* 03:01, B* 08:01, B* 15:01, B* 27.05, B* 52:01, C* 06:02, C*12: 02, DQB1* 03:01, DRB1* 03:01 and DRB1 shared epitope (SE) alleles (HLA-DRB1* 01:01, 01: 02, 04: 01, 04: 04, 04: 05, 04: 01: 08, 10:01, 14:02), they found that 61.5% of inflammatory arthritis irAEs patients had at least one SE allele, HLA DRB1* 04:05 was enriched in inflammatory arthritis irAEs.…”
Section: The Organ-specific Biomarkers Of Iraesmentioning
confidence: 72%